Tolerance and accumulation of lithium in Apocynum pictum Schrenk - Li Jiang; Lei Wang; Lei Zhang; Changyan Tian (PeerJ, 2018)
Primarily, lithium (Li) resource development and wider application of Li-ion batteries result in Li pollution and concomitantly poses increasing and inevitable problems to environmental health and safety. However, information is rare about the scope of the remediation of Li contaminated soil. Apocynum venetum is already proved to be a Li-accumulator with high Li tolerance and accumulation (Jiang et al., 2014). However, it is not clear whether Apocynum pictum, another species of the same genus with the same uses as A. venetum, is also a Li-accumulator. We investigated germination, growth and physiological responses of A. pictum to different levels of LiCl. Germination was not significantly affected by low Li concentration (0–100 mmol L−1). As LiCl increased from 100 to 400 mmol L−1, both germination percentage and index decreased gradually. For germination of A. pictum seeds, the critical value (when germination percentage is 50%) in LiCl solution was 235 mmol L−1, and the limit value (when germination percentage is 0%) was 406 mmol L−1. A. pictum could accumulate >1,800 mg kg−1 Li in leaves, and still survived under 400 mg kg-1 Li supply. The high Li tolerance of A. pictum during germination and growth stage was also reflected by activity of α-amylase and contents of soluble sugar, proline and photosynthetic pigments under different Li treatments. The bioconcentration factors (BCF) (except control) and translocation factors (TF) were higher than 1.0. High tolerance and accumulation of Li indicated that A. pictum is Li-accumulator. Therefore, this species could be useful for revegetation and phytoremediation of Li contaminated soil.